2013
DOI: 10.1016/j.bandl.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of letter identity and letter position are modulated by lexical frequency

Abstract: The encoding of letter position is a key aspect in all recently proposed models of visual-word recognition. We analyzed the impact of lexical frequency on letter position assignment by examining the temporal dynamics of lexical activation induced by pseudowords extracted from words of different frequencies. For each word (e.g., BRIDGE), we created two pseudowords: A transposed-letter (TL: BRIGDE) and a replaced-letter pseudoword (RL: BRITGE). ERPs were recorded while participants read words and pseudowords in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…(We acknowledge that the Bayesian Reader model does not make any claims on the specific time windows of these effects, because this is a formal model that focuses on word identification times and accuracy rates.) The present data are also consistent with the idea of uncertainty with respect to the order of the letters during word processing (Davis, 2010;Gomez, Ratcliff, & Perea, 2008;Vergara-Martínez, Perea, Gomez, & Swaab, 2013, for ERP evidence of the time course of transposed-letter effects). An avenue for future research would be to determine whether letter visual-similarity effects in a reading context occur in a purely bottom-up manner or whether they are modulated by higher level elements, such as the transitional probabilities of letters or top-down feedback from the lexical level (Dehaene & Cohen, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…(We acknowledge that the Bayesian Reader model does not make any claims on the specific time windows of these effects, because this is a formal model that focuses on word identification times and accuracy rates.) The present data are also consistent with the idea of uncertainty with respect to the order of the letters during word processing (Davis, 2010;Gomez, Ratcliff, & Perea, 2008;Vergara-Martínez, Perea, Gomez, & Swaab, 2013, for ERP evidence of the time course of transposed-letter effects). An avenue for future research would be to determine whether letter visual-similarity effects in a reading context occur in a purely bottom-up manner or whether they are modulated by higher level elements, such as the transitional probabilities of letters or top-down feedback from the lexical level (Dehaene & Cohen, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have found that the N400 component is also reduced following TL versus RL primes (Carreiras, Gillon-Dowens, Vergara, & Perea, 2009; Vergara-Martínez, Perea, Marín, & Carreiras, 2011), indicating that TL primes facilitate access to the word’s representation in semantic memory better than do RL primes. Finally, in a related pair of studies in which single words were fully viewed (without primes), TL nonwords again elicited facilitated N400 amplitudes relative to RL nonwords (Carrerias, Vergara, Perea, 2007), an effect that was more pronounced for higher frequency words (Vergara-Martínez et al, 2013). Together, then, the ERP evidence mirrors behavioral findings in showing that both orthographic and semantic processing are facilitated following TL versus RL nonwords and primes.…”
Section: Methodsmentioning
confidence: 92%
“…N400 responses to compound words have also been shown to be sensitive to constituent frequency (Vergara-Martínez, Perea, Gomez, & Swaab, 2013) and constituent lexicality (El Yagoubi, Chiarelli, Mondini, Danieli, & Semanza, 2008; c.f. Coch, Bares, & Landers, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have incorporated task manipulations (e.g. Chen, Davis, Pulvermüller, & Hauk, 2013 ; Kiefer & Martens, 2010 ; Strijkers, Bertrand, & Grainger, 2014 ; Vergara-Martínez, Perea, Gómez, & Swaab, 2013 ; Ziegler, Besson, Jacobs, Nazir, & Carr, 1997 ) and have shown that the nature of the task does modulate the pattern of ERPs. However, a common feature of all of these studies is that the choice of task has only a quantitative influence on either the magnitude or the precise timing of the ERPs.…”
mentioning
confidence: 99%